Using the candidacy framework to understand how doctor-patient interactions influence perceived eligibility to seek help for cancer alarm symptoms: a qualitative interview study - Sara Tookey; Cristina Renzi; Jo Waller; Christian von Wagner; Katriina L. Whitaker (BMC, 2018)
Abstract Background 'Candidacy' is concerned with the way people consider their eligibility for accessing health services. We used the Candidacy Framework to explore how the doctor-patient relationship can influence perceived eligibility to visit their General Practitioner (GP) among people experiencing cancer alarm symptoms. Methods We carried out a secondary analysis of qualitative interviews with 29 women and 33 men, aged ≥50 years experiencing cancer alarm symptoms, recruited through primary care. Interviews focused on symptom experience, help-seeking and primary care use. Framework analysis was used to analyse transcripts with a focus on GP-patient interactions. Results Perceived (im)permeability of services acted as a barrier to help-seeking, due to limited availability of appointments, time-limited communication and difficulties asserting candidacy. There was also a focal role of communication in building a positive doctor-patient relationship, with some participants describing resisting offers of appointments as a result of previous negative GP adjudication. These factors not only influenced the current consultation but had longer-term consequences for future consultation. Conclusions Candidacy provides a valuable theoretical framework to understand the interactional factors of the doctor-patient relationship which influence perceived eligibility to seek help for possible cancer alarm symptoms. We have highlighted areas for targeted interventions to improve patient-centred care and improve earlier diagnosis.